2021
DOI: 10.1080/10717544.2021.1872739
|View full text |Cite
|
Sign up to set email alerts
|

Ocular lamellar crystalline gels for sustained release and enhanced permeation of resveratrol against corneal neovascularization

Abstract: Corneal neovascularization (CNV) is the major cause of blindness after eye injury; however, only several drugs can be applied and the invasive administration ways (i.e., intravitreal injection and subconjunctival injection) are used. Resveratrol is a highly effective anti-VEGF agent against CNV. However, its applications are limited due to its strong hydrophobicity and instability. Here, we developed a resveratrol-loaded ocular lamellar crystalline gel (ROLG) for high inhibition of CNV. ROLGs were composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In presence of tested formulation, the epithelial and stroma structures were also maintained as unaltered, unlike what happens when porcine cornea was treated with a patch soaked in NaOH 0.1 N for 10 min (Fig. 7 c) confirming the great safety profile of GMO-based formulation for ophthalmic administration 36 , 37 . The desired and chemically induced damage led to an evident destruction of the corneal epithelium (black arrow) and a disorganization of stroma (white arrow).…”
Section: Resultsmentioning
confidence: 62%
“…In presence of tested formulation, the epithelial and stroma structures were also maintained as unaltered, unlike what happens when porcine cornea was treated with a patch soaked in NaOH 0.1 N for 10 min (Fig. 7 c) confirming the great safety profile of GMO-based formulation for ophthalmic administration 36 , 37 . The desired and chemically induced damage led to an evident destruction of the corneal epithelium (black arrow) and a disorganization of stroma (white arrow).…”
Section: Resultsmentioning
confidence: 62%
“…Resveratrol treatment had no effect on corneal epithelial thickness. A previous study found that once daily topical application of a resveratrol-loaded gel for 14 days following a corneal alkaline burn promoted recovery of the corneal epithelium in rats (Li M. et al, 2021). The current study only used 3 applications of resveratrol prior to and just after corneal abrasion and looked at one time point after abrasion.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been studies on the potential therapeutic effects of resveratrol in ocular diseases, although they have not focused on its analgesic properties (Abengozar-Vela et al, 2019;Li M. et al, 2021;Marino et al, 2013;Shetty et al, 2020;Tsai et al, 2015) (see reviews (Delmas et al, 2021;Fremont, 2000)).…”
Section: Introductionmentioning
confidence: 99%